2008
DOI: 10.1177/0020715208088909
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Entry of Turkish Immigrant Youth in Germany

Abstract: Drawing on three large datasets from the German Higher Education Information System Institute (HIS) from 1990, 1994 and 1999, the study reveals that Turkish youth are considerably more likely than Germans to enter tertiary education. This result sharply contrasts with fi ndings on the Turks' poor performance in primary and secondary school. The higher propensity for tertiary education among Turks can, to some degree, be explained by their lack of familiarity with the German system of dual vocational training a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
5
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 20 publications
7
102
5
21
Order By: Relevance
“…Research has shown that the fate of the 'second generation' is not as rosy as we may wish. Their educational qualifications often remain below those of the majority population, and their labour market performance is often poor (Fassmann 1997;Alba 2005;Meurs, Pailhé, and Simon 2006;Aparicio 2007;Brinbaum and Cebolla-Boado 2007;Van Niekerk 2007;Kristen, Reimer, and Kogan 2008;Aeberhardt et al 2010;Fibbi, Lerch, and Wanner 2007). The current study provides information on the demographic behaviour of important population subgroups in the UK and will improve our understanding of how various factors shape the fate of the 'second generation' in the European context.…”
Section: Introductionmentioning
confidence: 91%
“…Research has shown that the fate of the 'second generation' is not as rosy as we may wish. Their educational qualifications often remain below those of the majority population, and their labour market performance is often poor (Fassmann 1997;Alba 2005;Meurs, Pailhé, and Simon 2006;Aparicio 2007;Brinbaum and Cebolla-Boado 2007;Van Niekerk 2007;Kristen, Reimer, and Kogan 2008;Aeberhardt et al 2010;Fibbi, Lerch, and Wanner 2007). The current study provides information on the demographic behaviour of important population subgroups in the UK and will improve our understanding of how various factors shape the fate of the 'second generation' in the European context.…”
Section: Introductionmentioning
confidence: 91%
“…This is important because studies have found that stereotype threat effects can lead to VERTICAL COLLECTIVISM AND STEREOTYPE THREAT 21 disengagement with the academic domain (Schmader, Major, & Gramzow, 2001), which might amplify educational disadvantages (e.g., Kristen et al, 2008). Second, the deployment of these temporary individual mobility strategies should be valued by their own group because it is consistent with the group's achievement expectations (Phalet & Claeys, 1993), and thus should reduce potential worries about not living up to the group's expectations.…”
Section: Effects Of Coping Strategiesmentioning
confidence: 99%
“…Today, children of Turkish-origin migrants perform more poorly in standardized tests than Germans and other migrant groups (e.g., Bos, 2012;Klieme et al, 2010;Mok, Martiny, Gleibs, Keller, & Froehlich, 2016) and are less likely to attain higher education (e.g., Kristen, Reimer, & Kogan, 2008). On the one hand this underperformance is surprising, because research shows that the Turkish culture strongly values achievement motivation (e.g., Phalet & Claeys, 1993;Verkuyten, Thijs, & Canatan 2001), and high achievement motivation and good performance outcomes are expected from Turkish students by their families (Phalet & Claeys, 1993).…”
mentioning
confidence: 99%
“…Research has shown that the social mobility of the second generation is not as large as we may wish. Their educational qualifications often remain lower than those of the majority population in European countries, and their labour market performance is often poor (Aeberhardt et al 2010;Alba 2005;Aparicio 2007;Brinbaum and Cebolla-Boado 2007;Fibbi, Lerch, and Wanner 2007;Kristen, Reimer, and Kogan 2008;Meurs, Pailhé, and Simon 2006;Van Niekerk 2007). The studies presented provide information on the family behaviour of these population subgroups in Europe, improving our understanding of how various factors shape the lives of the second generation in the European context.…”
Section: Advances In Research On Immigrant and Ethnic Minority Familiesmentioning
confidence: 94%